1997
DOI: 10.1002/(sici)1521-186x(1997)18:7<499::aid-bem5>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Stress proteins are not induced in mammalian cells exposed to radiofrequency or microwave radiation

Abstract: The induction of stress proteins in HeLa and CHO cells was investigated following a 2 h exposure to radiofrequency (RF) or microwave radiation. Cells were exposed or sham exposed in vitro under isothermal (37 ± 0.2 °C) conditions. HeLa cells were exposed to 27‐ or 2450 MHz continuous wave (CW) radiation at a specific absorption rate (SAR) of 25 W/kg. CHO cells were exposed to CW 27 MHz radiation at a SAR of 100 W/kg. Parallel positive control studies included 2 h exposure of HeLa or CHO cells to 40 °C or to 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Twenty-four hours after exposure, however, there appeared to be no alteration in the amount of Hsp70 protein in these brain areas (detected by immunocytochemical analysis) indicating that the effect was short-lived and not significant. Microwave or RF radiation had no detectable effect on the levels of stress proteins within HeLa and CHO cells following a 2 h exposure to 27 MHz or 2450 MHz continuous wave radiation (Cleary et al, 1997). Our result is also in agreement with the theory proposed by Laurence et al (2000); that low power, pulsed RF fields (much like that used for this project) are insufficient to induce a heat shock response.…”
Section: Rf Fields Did Not Induce a Heat Shock Response In Sk-n-sh Cellssupporting
confidence: 91%
“…Twenty-four hours after exposure, however, there appeared to be no alteration in the amount of Hsp70 protein in these brain areas (detected by immunocytochemical analysis) indicating that the effect was short-lived and not significant. Microwave or RF radiation had no detectable effect on the levels of stress proteins within HeLa and CHO cells following a 2 h exposure to 27 MHz or 2450 MHz continuous wave radiation (Cleary et al, 1997). Our result is also in agreement with the theory proposed by Laurence et al (2000); that low power, pulsed RF fields (much like that used for this project) are insufficient to induce a heat shock response.…”
Section: Rf Fields Did Not Induce a Heat Shock Response In Sk-n-sh Cellssupporting
confidence: 91%
“…Tian et al [2002], found an increase of Hsp70 at very high SARs in MO54 cells exposed to 2.45 GHz fields, but no effect in SARs considered safe for daily exposures (<5 W/kg). Even at similarly high SARs (25 or 100 W/kg), Cleary et al [1997] did not see Hsp70 production in CHO or HeLa cells 24 h following exposure to 27 or 2450 MHz radiation. Fritze et al [1997] found a small increase in HSP70 mRNA following a 4 h exposure to $900 MHz GSM signal at 7.5 W/kg SAR, but not at lower SARs.…”
Section: Mechanisms: Heat Shock Proteinsmentioning
confidence: 81%
“…In the literature, reports of RF effects on heat-shock protein (HSP) expression are divided fairly evenly between those that find no detectable effect [e.g. Cleary et al, 1997;Laszlo et al, 2005;Lim et al, 2005;Lantow et al, 2006;Chauhan et al, 2006a, b], except at high SARs where thermal effects are clearly implicated , and those where one or more HSPs appear to be induced [e.g. Kwee et al, 2001;Shallom et al, 2002;Leszczynski et al, 2002;Weisbrot et al, 2003;reviewed Belyaev, 2005].…”
Section: Introductionmentioning
confidence: 99%